Meaningful learning applied to communication university teaching in Spain during the pandemic. An asynchronous collaborative experience - Castro-Martínez, Andrea; Pérez-Ordóñez, Cristina de los Ángeles (My University, 2022)
The pandemic led education systems to switch immediately to online learning, in many cases without the necessary period of design and adaptation of teaching tools. In many cases with no specific training in online teaching, the lecturers had to adapt their classes to a permanent virtual space, usually abusing synchronous teaching. This literal adaptation of the methodologies used in the classroom to the online learning scene, in addition to aspects such as periods of lock-in, required physical distance and overexposure to digital media, have caused significant tiredness among students, who reported difficulties in maintaining their attention in synchronous lectures. This paper presents a proposal implemented in 5 subjects of Spanish communication degrees by two professors who had previous experience in e-learning education. Our aim is analysing the usefulness of class diary writing in a collaborative and asynchronous process for each student in the whole class. For studying this tool, two methods have been developed in each of the subjects: the participant observation and satisfaction surveys on the use of the personal diary.
Keywords: Tecnología educativa - Congresos; E-learning; Pandemic; COVID-19; Teaching; Digital teaching